Spatial Heterogeneity in the Photosynthetic Characteristics of Scleractinian coral Symbiodinium from the Northern South China Sea - Zhang Shuqi; Zhong Yu; Zheng Xiaoyun; Guo Pu; Zhao Meixia; Yan Hongqiang; Shi Qi (Redai dili, 2025)
Investigations have revealed significant degradation of nearshore coral reef areas in the South China Sea in recent decades; thus, coral reef conservation is in urgent need of more scientific management insights. The health of coral reef ecosystems can be effectively assessed by utilizing the photosynthetic ecological parameters of zooxanthellae, which are symbiotic with scleractinian corals. In this study, six genera of scleractinian corals (Platygyra, Dipsastraea, Favites, Porites, Acropora, and Pavona) from Weizhou Island, Daya Bay, and Wanshan Archipelago in the northern part of the South China Sea were experimentally studied. Three physiological parameters, namely the density of coral symbiotic zooxanthellae, chlorophyll-a content, and photosynthetically effective quantum yield (ΦPSII), were measured to understand the photosynthetic characteristics of scleractinian coral symbionts in relatively high-latitude corals, compare their intergeneric differences among different coral morphologies, and explore the ecological effects of environmental factors by analyzing spatial similarities and differences. The study results are as follows: First, a one-way analysis of variance and non-parametric tests based on the division of individual coral distribution areas showed overall significant spatial differences in the density and chlorophyll-a content of scleractinian corals' zooxanthellae from the Weizhou Island and Daya Bay (P≤0.01); no significant spatial differences were observed in the physiological parameters of photosynthesis for those from the Daya Bay and Zhuhai's Wanshan Archipelago; Redundancy analysis(RDA) analyses indicated that Sea Surface Temperature(SST) was the most important environmental factor affecting the density and chlorophyll-a content of the coral symbiotic zooxanthellae. Due to its unique geographical location and environmental factors, the ecological status of coral communities in the Daya Bay is well-maintained with higher density and chlorophyll-a content of symbiotic zooxanthellae in the relatively high-latitude sea area. Second, the density and chlorophyll-a content of the zooxanthellae of Platygyra from the Daya Bay were significantly higher than those of Acropora and Pavona. Coral morphology may be a key driver influencing the relationship between density and photosynthesis of the symbiotic zooxanthellae. Massive corals generally had higher symbiotic zooxanthellae density and chlorophyll-a content and showed greater tolerance to thermal stress than branching corals. Under similar morphologies, significant interspecific differences in the density of symbiotic zooxanthellae in corals were also observed, which may be related to their unique skeletal structures and physiological characteristics. These findings reveal that the physiological responses of scleractinian corals and their symbiotic zooxanthellae to environmental changes are not fixed, and that coral morphology and interspecific differences have complex effects on their ecological adaptations.